TRANSFORMASI MAKNA DAN NILAI TRADISI BAROAH DAYAK KANAYATN DUSUN SEMANGKILING KECAMATAN MANDOR KABUPATEN LANDAK - Linda, Linda; Sastrawan Noor, Agus; Khosmas, F. Y. (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractSemangkiling Hamlet is one of the hamlets located in Bebatung Village, Mandor District, Landak Regency. This hamlet has a multicultural society. Despite having a multicultural society, this hamlet still holds fast to their traditions that have existed for a long time, one of which was the baroah tradition. This tradition is routinely carried out every year, but along with the times the tradition of baroah experiences changes in meaning and value as happened in the Semangkiling Hamlet community. The method used in this research is descriptive method with a qualitative research form. The technique in this study uses four techniques namely observation, data collection, documentation, and literature. The results of this study indicate: (1). The background of the implementation of baroah tradition in Semangkiling Hamlet is in the form of three, namely: the majority aspects of an agrarian society, the religious aspects of the community, the social aspects of the Semangkiling community, (2). The process of implementing the Baroah tradition in Semangkiling is bahaump, coughing, humping ', meaning of roah. (3). Transformation of the Meaning and Value of the Baroah Tradition took place before and after the entry of Christianity, especially Protestantism. the factors that cause a shift in meaning and value that occur are religious factors, economic factors, and social factors in the Semangkiling hamlet community. The meaning and value of the baroah tradition in Semangkiling Hamlet, which is no longer entirely religious, is only an annual routine. Keywords: Transformation, Meaning and Value, Baroah Tradition.